Model-Based Safety and Assessment 4th International Symposium, IMBSA 2014, Munich, Germany, October 27-29, 2014, Proceedings - Ortmeier, Frank; Rauzy, Antoine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the 4th International Symposium on Model-Based Safety and Assessment, IMBSA 2014, held in Munich, Germany, in October 2014. The 15 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on modeling paradigms, validation and testing, fault detection and handling, safety assessment in the automotive domain, and case studies.
Modeling Paradigms -- Validation and Testing -- Fault Detection and Handling -- Safety Assessment in the Automotive Domain -- Case Studies.
Keywords: Computer science; Software engineering; Machine theory; Compilers (Computer programs).; Algorithms; Computer Science Logic and Foundations of Programming; Software Engineering; Formal Languages and Automata Theory; Compilers and Interpreters; Algorithms